2015
DOI: 10.1158/1940-6207.capr-14-0347
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Chemically Induced Urinary Bladder Cancers by Naproxen: Protocols to Reduce Gastric Toxicity in Humans Do Not Alter Preventive Efficacy

Abstract: The COX inhibitors (NSAIDs/Coxibs) are a major focus for the chemoprevention of cancer. The COX-2 specific inhibitors have progressed to clinical trials, and have shown preventive efficacy in colon and skin cancers. However, they have significant adverse cardiovascular (CV) effects. Certain NSAIDs (e.g., naproxen (NPX)] have a good cardiac profile, but can cause gastric toxicity. The present studies examined protocols to reduce this toxicity of NPX. Female Fischer-344 rats were treated weekly with the urinary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The study was a single center randomized, doubleblinded trial to determine the modulatory effects of intermittent ASA dosing (ASA 81 mg daily for one week alternating with placebo daily for one week) versus continuous ASA dosing (ASA 81 mg daily) for 12 weeks on nasal epithelium gene expression and arachidonic acid metabolism in current smokers. The intermittent schedule (1 week on/1 week off) was designed on the basis of pre-clinical studies of potentially less toxic, alternative drug-dosing schedules, including studies of naproxen that showed equivalent efficacy of this weekly intermittent dosing schedule to daily continuous dosing in rodent models of urinary bladder and colon carcinogenesis (16,17). The primary endpoint was treatmentassociated modulation of a smoking-associated geneexpression signature derived using bronchial and nasal brushings (n ¼ 119 genes; ref.…”
Section: Methodsmentioning
confidence: 99%
“…The study was a single center randomized, doubleblinded trial to determine the modulatory effects of intermittent ASA dosing (ASA 81 mg daily for one week alternating with placebo daily for one week) versus continuous ASA dosing (ASA 81 mg daily) for 12 weeks on nasal epithelium gene expression and arachidonic acid metabolism in current smokers. The intermittent schedule (1 week on/1 week off) was designed on the basis of pre-clinical studies of potentially less toxic, alternative drug-dosing schedules, including studies of naproxen that showed equivalent efficacy of this weekly intermittent dosing schedule to daily continuous dosing in rodent models of urinary bladder and colon carcinogenesis (16,17). The primary endpoint was treatmentassociated modulation of a smoking-associated geneexpression signature derived using bronchial and nasal brushings (n ¼ 119 genes; ref.…”
Section: Methodsmentioning
confidence: 99%
“…It is thought to study by reducing the action of cyclooxygenase (COX) included in the production of prostaglandins that are manufactured in answer to certain diseases or injury and cause pain, inflammation and swelling [2]. As well as other NSAIDs, naproxen was reported to be efficient in the prevention of many cancers [3][4][5]. Hydrazide-hydrazones [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and 1,2,4-triazole rings [22][23][24][25][26] have diverse biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclooxygenase (COX) inhibitors have been investigated for chemopreventive activity in reducing the occurrence of bladder cancer [ 12–23 ], for antitumor effects against established bladder cancer [ 14, 15, 24–37 ], and for effects in enhancing chemotherapy [ 24, 26, 28–30, 38 ], with positive results in most, but not all studies. Several mechanisms of the antitumor activity of COX inhibitors have been proposed including direct induction of apoptosis [ 27, 38, 39 ], immunomodulatory effects [ 25, 24, 40 ], antiangiogenic activity [ 40 ], changes in microRNAs [ 41 ], and inhibitory effects on cancer stem cells [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms of the antitumor activity of COX inhibitors have been proposed including direct induction of apoptosis [ 27, 38, 39 ], immunomodulatory effects [ 25, 24, 40 ], antiangiogenic activity [ 40 ], changes in microRNAs [ 41 ], and inhibitory effects on cancer stem cells [ 37 ]. Studies have been performed in rodents with experimentally-induced bladder tumors [ 12–15, 24, 37 ], in humans in epidemiological and clinical studies [ 16–23, 35, 36, 38 ], and in dogs with naturally-occurring UC (high grade invasive urothelial carcinoma or transitional cell carcinoma) [ 25–34 ]. UC in dogs closely mimics invasive bladder cancer in humans with regards to cellular and molecular characteristics including COX-2 expression, local cancer invasion, distant metastases, and response to chemotherapy [ 42 ].…”
Section: Introductionmentioning
confidence: 99%